Complications In The Management Of High-Energy Closed Fractures Of Proximal Tibial Plateau. A Retrospective Study - Akhtar, Rahman Rasool; Ali, Waqas; Ahmed, Riaz; Kashmiri, Muhammad Nadeem; Waris, Hira; Haider, Muhammad (Journal of Rawalpindi Medical College, 2023)
Objective: To analyze the management of high-energy Schatzker type V and VI tibial plateau fractures which are associated with infectious and noninfectious complications. Methods: This study was carried out in the Department of Orthopedic Surgery, Rawalpindi Medical University from July 1, 2018, to June 30, 2021. This is a retrospective study which is done in three years. Patients had to be between the ages of 18 and 60, have no history of arthritis, have a closed fracture of the proximal tibia (Schatzker type V and VI), or have AO type 41-C1, C2 or C3 involvement of the lower limb. Each patient received treatment using techniques such as internal fixation with locking plates and open reduction which are minimally invasive. Results: This study involved a total of 132 patients.Mean age was 35.15±10.59.115(87%) were men and 17(13%) were women out of 132. A total of 39 out of 132 patients experienced complications (29.54%). Infectious complications (18.93%) were found in (25/132) patients 16 out of 25 patients had superficial infections. Routine dressing changes and antibiotic treatment were carried out in patients who had superficial infections.9 out of 25 patients who had faced a deep-seated infection underwent repeated implant removal, debridements, amputation, and flap covering depending on the reaction of the host. Noninfectious complications had been reported in 14 patients(10.6%). Six patients had hardware-related issues and four of them required a secondary treatment.08 individuals had malalignment, with five of them having it in their immediate postoperative radiographs and three others having it in their late postoperative radiographs. Conclusion: In closed wounds, substantial soft tissue destruction is linked to the fractures of the proximal tibial plateau, particularly Shatzker type V and VI. By selecting the right patients and minimising soft tissue dissection, the problems related to the management of these fractures can be reduced. Keywords: Proximal tibial plateau, Malalignment, Infectious complications, Debridement, Schatzker type V and VI.